THE INFLUENCE OF WORKLOAD, JOB STRESS, AND EFFECTIVE COMMUNICATION TOWARDS EMPLOYEE’S PRODUCTIVITY AT CV.KOMBOS MANADO - Suoth, Jonathan G.; Saerang, David P.E; Tumiwa, Johan R. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: The Wheel of Life of an employee is one important concept that can easily be put off balance by the quality of work and work related stress. Effective communication also plays a vital role in the company that can influence the employee’s productivity. Productivity increases when your employees are satisfied with their jobs and with the level of communication they receive from management. In north Sulawesi, PT. Hasrjat Abadi has several branches office which is located in different region, one of the branches is CV. Kombos. This research aim to know about the influence of workload, job stress, and effective communication toward employees’ productivity. This research is using a multiple regression analysis with total population is 50 employees at CV. Kombos Manado. The result shows that workload and effective communication are significantly influence the employees’ productivity. Meanwhile, job stress isn’t significantly influence the employees’ productivity. The company should keep added the something that can keep the productivity of the employee positively increase, like hire a professional team leader. Also, create a good communication toward the employees. Keywords: workload, job stress, effective communication, employee productivity